INTRODUKSI PRODUKSI BENIH MELALUI TEKNIK FISI PADA KELOMPOK PEMBUDIDAYA TERIPANG (Stichopus sp.) DI KAMPUNG MADONG, KELURAHAN KAMPUNG BUGIS, KOTA TANJUNGPINANG - Muzahar, Muzahar; Bakkara, Okto Rimandi; Putri, Dwi Septiani; Miranti, Shavika; Wulandari, Rika; Yulianto, Tri; Irawan, Henky; Raza’i, Tengku Said (Universitas Mataram, 2025)
Sea cucumbers are members of the Phylum Echinodermata which have high economic value and widely used by the coastal communities of the Riau Islands as food sources and medicines. Unregulated fishing greatly pressure sea cucumber populations in natural waters. Aquculture is regarded as a solution to the over-exploitation of sea cucumbers from natural waters. However, further research is needed to establish the better technical and economic efficiency. Local sea cucumber farmer needs information about the technical aspects of sea cucumber seed production so they can produce the seeds independently. Therefore, a series of dissemination and demonstrations were organized to introduce the method of produce sea cucumber seeds using the fission technique. This community service activity was carried out using the participatory action research (PAR) method involving the Maju Mandiri fish farmer group in Kampung Madong, Kampung Bugis Village, Tanjungpinang City. The team carried out counseling and demonstrated the binding procedure to simulate fission in sea cucumber. Our partner group seemed enthusiastic about participating in the activity and quite proficient on some basic fission techniques to provide sea cucumber seeds. This activity also raises awareness among the locals to actively maintain the sustainability of marine resources. So, we hope our partner group can start the sea cucumber culture business with independent seed production, and they can achieve our goals to improving community welfare and preserving the water environment simultaneously.